American lit - Seltzer, Richard (West Roxbury, Mass. B&R Samizdat Express, 2001)
The CD contains 530 books featuring a cross section of American literature, before 1920, from the works of Louisa Mae Alcott to the works of Zane Grey.
System requirements: Windows PC, with Web Browser and/or Word.
Keywords: American literature -- Collections